COMPUTER ANALYSIS OF THE STRUCTURES OF LIPASES FROM Geobacillus BACTERIA AND IDENTIFICATION OF MOTIFS DETERMINING THEIR THERMOSTABILITY - K. N. Sorokina; M. A. Nuriddinov; A. S. Rozanov; V. A. Ivanisenko; S. E. Peltek (Вавиловский журнал генетики и селекции)
Properties of thermostable lipases from Geobacillus bacteria are considered. The enzymes are divided into groups with regard to their thermostability. Coordinated amino acid substitutions are demonstrated in the highly thermostable group (half-inactivation time > 1000 min); V198A, Q203E, V204I, Q217E; and V294I, P306A, T307A, D312S, R313H, E316G, V324I, S334N, A343T. The hydrophilic moment of α helices, correlating with the charge and polarity of amino acid in the region, exerts the most significant influence on enzyme thermostability. Most thermostable lipases are characterized by structural stabilization of the lid domain in the 198А-217Е region.